Risk Sharing and Financial Contagion in Asia : An Asset Price Perspective - Rungcharoenkitkul, Phurichai (Washington, D.C. : International Monetary Fund, 2011)
This paper assesses financial integration in Asia in terms of risk-sharing benefit versus financial-contagion cost. We construct a new measure of risk sharing based on a term structure model, which allows identification of realized stochastic discount factors. Risk sharing is low in Asia, and varies across time and countries, whereas contagion risks are more significant intra-regionally, and relatively stable over the past decade. An overall tradeoff exists between risk sharing and contagion, but the terms of tradeoffs vary across countries, depending on relative economic fluctuations and inflation differentials. Asia, therefore, can potentially enhance risk sharing without raising contagion risk.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet